Seasonality of the incidence of bronchiolitis in infants - Brazil, 2016-2022: An interrupted time-series analysis - Frederico Friedrich; Magali Santos Lumertz; Lucas Montiel Petry; Marina Puerari Pieta; Luana Braga Bittencourt; Bruno Brocker Nunes; Laura de Castro e Garcia; Marcos Otávio Brum Antunes; Marcelo Comerlato Scotta; Renato Tetelbom Stein; Marcus Herbert Jones; Talitha Comaru; et al. (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To evaluate the seasonality of acute bronchiolitis in Brazil during the 2020-2022 season and compare it with the previous seasons. Methods: Data from the incidence of hospitalizations due to acute bronchiolitis in infants <1 year of age were obtained from the Department of Informatics of the Brazilian Public Health database for the period between 2016 and 2022. These data were also analyzed by macro-regions of Brazil (North, Northeast, Southeast, South, and Midwest). To describe seasonal and trend characteristics over time, we used the Seasonal Autoregressive Integrated Moving Averages Model. Results: Compared to the pre-COVID-19 period, the incidence of hospitalizations related to acute bronchiolitis decreased by 97% during non-pharmacological interventions (March 2020 - August 2021) but increased by 95% after non-pharmacological interventions relaxation (September 2021 - December 2022), resulting in a 16% overall increase. During the pre-COVID-19 period, hospitalizations for acute bronchiolitis followed a seasonal pattern, which was disrupted in 2020-2021 but recovered in 2022, with a peak occurring in May, approximately 4% higher than the pre-COVID-19 peak. Conclusions: This study underscores the significant influence of COVID-19 interventions on acute bronchiolitis hospitalizations in Brazil. The restoration of a seasonal pattern in 2022 highlights the interplay between public health measures and respiratory illness dynamics in young children.